Construction and validation of an algorithm for disinfection of ambulances transporting patients with contagious infectious diseases - Geraldo Magela Salomé (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to develop and validate an algorithm to guide professionals in cleaning and disinfecting ambulances after transferring patients with contagious infectious diseases. Methods: the study was conducted between September and November 2021. The developed algorithm was validated by 104 judges, including nurses, physical therapists, and physicians who care for patients with contagious infectious diseases. It used the Delphi technique and content validity index. Results: in the first evaluation, the judges considered the algorithm "unsuitable" and "fully suitable". The algorithm reviewed according to the judges' suggestions was rated between "suitable" and "fully suitable" in the second evaluation. The overall content validity index was 0.960 and 0.998 in the first and second evaluations. Conclusions: the algorithm to guide the cleaning and disinfection of ambulances after transferring patients with contagious infectious diseases was developed and validated by specialists in the field, with consensus among the judges in the second evaluation.